Citizen observatories: Concept, opportunities and communication with citizens in the first EU experiences - Montargil, Filipe (2019)
This presentation discusses the emerging concept of Citizen observatories (COs), explores the opportunities it represents for public authorities to go beyond incremental bureaucratic innovation and presents the ﬁrst generation of European-funded experiences, held between 2012 and 2016. In the 2012–2016 period ﬁve CO projects have been funded by the EU, covering different areas: natural waters monitoring, odour monitoring, air quality monitoring, ﬂood risk management and a platform for citizen science surveys. These COs allowed to develop and test the concept’s implementation, although the societal impact is still very limited, involving a reduced number of users. These projects have, however, established a very valuable set of resources, knowledge and expertise. Although there is an economic rationale behind it, this is an emerging ﬁeld with interesting perspectives and possibilities, enclosing the possibility of using ICT in the creation of a relation between public authorities and citizens that can produce a valuable return for citizens.